Rehabilitation of a Grossly Decayed Premolar with a Custom Modified Fibre Post and Zirconia Crown - Ketaki Natarajan; Neha S. Dhaded; Sonal B. Joshi; Saloni Chougule; Pranav Machave (Oral Sphere Journal of Dental and Health Sciences, 2025)
Background: Using materials like metals and fiber-reinforced composites, intra-radicular posts are frequently utilised to reconstruct teeth that have suffered severe loss of coronal structure. Metal posts are less favoured due to esthetic limitations and mechanical incompatibility with dentin. Prefabricated fibre posts often poorly adapt to irregular canal shapes, leading to cement voids and compromised retention. Customising fibre posts to canal anatomy improves fit, reduces cement thickness, and enhances long-term prognosis. Case presentation: In this case study, a 53-year-old man with a severely decaying, previously endodontically treated upper right second premolar (tooth 15) exhibiting loss of crown structure and a periapical lesion is described as having been successfully managed. Clinical and radiographic evaluation confirmed no pain, swelling, or sinus tract. The tooth was isolated, and retreatment was initiated with canal cleaning, disinfection, and calcium hydroxide dressing, followed by obturation with AH Plus and gutta percha. A post space was prepared, and a prefabricated fibre post was customized using composite resin to replicate canal anatomy. A composite core was constructed after the relined post was light-cured and sealed with dual-cure resin cement. After a week, a zirconia crown was cemented. A three-month follow-up revealed outstanding post-adjustment and full periapical recovery. Conclusion: Customizing prefabricated fibre posts to match root canal anatomy enhances retention, stress distribution, and preserves radicular dentin. This technique offers a minimally invasive, esthetic, and mechanically superior alternative to conventional posts. Long-term studies are needed to validate its clinical efficacy further.